HIV/AIDS-Related Knowledge and Attitudes Among Chinese College Students and Associated Factors: A Cross-Sectional Study - Zhang, Ling; Yu, Hang; Luo, Hong; Rong, Wenlong; Meng, Xianxin; Du, Xiaoan; Tan, Xiaodong (Frontiers in Public Health, 2022)
In recent years, adolescent has become one of the high-risk groups for HIV. Meanwhile, good HIV awareness and positive attitude are essential for HIV prevention. This study aims to evaluate the extent to which college students understand HIV and their attitudes toward HIV-infected patients, as well as the correlative factors. The data used in this study came from a cross-sectional survey. An anonymous online questionnaire was used to investigate the demographic characteristics, HIV/AIDS-related knowledge, and attitudes toward HIV-infected patients of 17,678 students from a university in Henan. Descriptive statistics, Chi-square test and logistic regression were used to analyze differences and connections between variables in SPSS version 25.0. Participants' HIV/AIDS-related knowledge awareness rate was 80.8%. Levels of students' HIV/AIDS-related knowledge correlated with their gender, nationality, marital status, and their grade (p < 0.01). Female students [OR = 0.757, 95% CI (0.699–0.820)] and minority students (OR = 0.717, 95% CI (0.619–0.832)] had insufficient HIV health education knowledge. Meanwhile, male students (OR = 0.845, 95% CI (0.773–0.924)], and students with good HIV knowledge (OR unaware-ness/awareness = 2.385, 95% CI (2.111–2.694)] were more likely to hold a positive attitude toward HIV-infected patients. The relevant education departments should strengthen and promote the education of AIDS transmission and prevention. Many college students still hold negative attitude toward HIV-infected patients. The government should further make efforts to eliminate social discrimination in HIV-infected patients and lead people to approach HIV-infected patients fairly.